Model wzrostu dla modrzewia europejskiego (Larix decidua Mill.) wykorzystujący cechy taksacyjne drzewostanu - Bruchwald, Arkadiusz; Dmyterko, Elżbieta; Wojtan, Rafał (Leśne Prace Badawcze, 2011)
Data from each forest stand in all the Forest Districts in Poland (about 2.5 million stands) are available in the State Forests Information System (SILP). These data can be used to predict the development of timber resources and to drive growth models that determine the possibility of harvesting timber in pre-final and final felling. The Polish growth models used are individual-tree growth models consisting of four main algorithms: initial (W), thinning (T), tree mortality (S) and incremental (P). The model consists of several variants, differing only in their initial algorithm. The aim of this study is to describe an algorithm for one of the growth model variants for larch stands. The growth model variant presented employs the following characteristics of a stand as input data: mean age (W), average diameter breast height (Dg), average height (Hg), and stocking density (Zad). These data are used to generate the distribution of diameter breast heights of trees and assign an appropriate height to each tree. This enables the other growth model algorithms to subsequently be used to predict the development of larch timber resources. In Poland, growth models have been built for the following trees species: pine, spruce, fir, oak, beech, alder and birch. The growth model for larch stands completes the list and opens new research perspectives. Linking this model with those built for other tree species will lead to the development of a model for mixed stands and then for uneven-aged stands.